Phenotype heterogeneity of congenital adrenal hyperplasia due to genetic mosaicism and concomitant nephrogenic diabetes insipidus in a sibling - Yılmaz Kor; Minjing Zou; Roua A. Al-Rijjal; Dorota Monies; Brian F. Meyer; Yufei Shi (BMC, 2018)
Abstract Background Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21OHD) is an autosomal recessive disorder caused by mutations in the CYP21A2. Congenital nephrogenic diabetes insipidus (NDI) is a rare X-linked recessive or autosomal recessive disorder caused by mutations in either AVPR2 or AQP2. Genotype-phenotype discordance caused by genetic mosaicism in CAH patients has not been reported, nor the concomitant CAH and NDI. Case presentation We investigated a patient with concomitant CAH and NDI from a consanguineous family. She (S-1) presented with clitoromegaly at 3 month of age, and polydipsia and polyuria at 13 month of age. Her parents and two elder sisters (S-2 and S-3) were clinically normal, but elevated levels of serum 17-hydroxyprogesterone (17-OHP) were observed in the mother and S-2. The coding region of CYP21A2 and AQP2 were analyzed by PCR-sequencing analysis to identify genetic defects. Two homozygous CYP21A2 mutations (p.R357W and p.P454S) were identified in the proband and her mother and S-2. The apparent genotype-phenotype discordance was due to presence of small amount of wild-type CYP21A2 alleles in S-1, S-2, and their mother's genome, thus protecting them from development of classic form of 21OHD (C21OHD). A homozygous AQP2 mutation (p.A147T) was also found in the patient. The patient was treated with hydrocortisone and hydrochlorothiazide. Her symptoms were improved with normal laboratory findings. The clitoromegaly is persisted. Conclusions Genetic mosaicism is a novel mechanism contributing to the genotype-phenotype discordance in 21OHD and small percentage of wild-type CYP21A2 alleles may be sufficient to prevent phenotype development. This is a first report of concurrent 21OHD and NDI caused by simultaneous homozygous CYP21A2 and AQP2 mutations.